2021
DOI: 10.1186/s12974-021-02306-9
|View full text |Cite
|
Sign up to set email alerts
|

Carnosine quenches the reactive carbonyl acrolein in the central nervous system and attenuates autoimmune neuroinflammation

Abstract: Background Multiple sclerosis (MS) is a chronic autoimmune disease driven by sustained inflammation in the central nervous system. One of the pathological hallmarks of MS is extensive free radical production. However, the subsequent generation, potential pathological role, and detoxification of different lipid peroxidation-derived reactive carbonyl species during neuroinflammation are unclear, as are the therapeutic benefits of carbonyl quenchers. Here, we investigated the reactive carbonyl acr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(40 citation statements)
references
References 80 publications
2
35
0
Order By: Relevance
“…In studies involving oral (drinking water) administration, one of the two “often used” ( Figure 1 ) administration routes, the dosage amounts vary widely, ranging from 0.5 g/L [ 98 , 116 ] to 30 g/L (60 times higher!) [ 109 , 118 ]. Furthermore, in the context of oral administration, at least five different units of measurement can be found within the research studies: mg or g/Kg [ 119 , 120 , 121 ], mg or g/L [ 98 , 115 , 116 ], mmol/L or Kg [ 99 , 122 , 123 , 124 ], mM [ 102 , 125 , 126 ], or % [ 127 , 128 , 129 ].…”
Section: In Vivo Preclinical Studies: Administration Route Dosage Tre...mentioning
confidence: 99%
“…In studies involving oral (drinking water) administration, one of the two “often used” ( Figure 1 ) administration routes, the dosage amounts vary widely, ranging from 0.5 g/L [ 98 , 116 ] to 30 g/L (60 times higher!) [ 109 , 118 ]. Furthermore, in the context of oral administration, at least five different units of measurement can be found within the research studies: mg or g/Kg [ 119 , 120 , 121 ], mg or g/L [ 98 , 115 , 116 ], mmol/L or Kg [ 99 , 122 , 123 , 124 ], mM [ 102 , 125 , 126 ], or % [ 127 , 128 , 129 ].…”
Section: In Vivo Preclinical Studies: Administration Route Dosage Tre...mentioning
confidence: 99%
“…According to our previous study, ACR could also destroy the insulin receptor signaling pathway, resulting in impaired glucose homeostasis ( Qi et al, 2021 ). In order to distinguish destructive neurogenesis in ACR treated embryos resulting from impaired glucose homeostasis or ACR itself, anti-ACR drug (L-carnosine) ( Zhao et al, 2019 ; Spaas et al, 2021 ) and hypoglycemic drug (PK11195) ( Wiggenhauser et al, 2020 ) were utilized. Interestingly, anti-ACR, but not hypoglycemic treatment, could rescue the shortened motor nerves ( Figure 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…Several studies, reviewed by Boldyrev et al ( 2013 ), have demonstrated that carnosine can reduce oxidative stress in vitro and in vivo. The anti-oxidant activity of carnosine is based on its reaction with superoxide anions (Kohen et al 1991 ; Klebanov et al 1997 ), reactive aldehydes like HNE and acrolein (Aldini et al 2002 ; Baba et al 2013 ; Zhao et al 2019 ; Spaas et al 2021 ) or carbonyl groups in oxidized proteins (Hipkiss et al 2001 ). Carnosine may also increase activity of anti-oxidant enzymes, such as superoxide dismutase or glutathione peroxidase (Kim et al 2011 ).…”
Section: Discussionmentioning
confidence: 99%